Effect of diabase intrusion on the CBM-bearing coalfields of southern Brazil: A review. (November 2022) - Bicca, M.M.; Kalkreuth, W.; Rosa, A.L.; Simão, G.; Levandowski, J.; Silva, T.F.; Anzolin, H.M.
Abstract: The Paraná Basin coalfields of southern Brazil belong to the Permian Gondwana I Supersequence interval. The coals generally experienced low burial temperatures at the basin edges, but local igneous intrusions of the Paraná superplume (Cretaceous) altered their previous thermal conditions. The Santa Terezinha, Chico-Lomã, and Morungava coalfields are considered to be the most proliferous thermally altered deposits for Coalbed Methane (CBM) prospection in the south of Brazil. To better understand the coalification process for these unconventional gas reservoirs, the present review presents a compilation of vitrinite reflectance (VR) measurements generated in earlier studies, coal petrological characteristics, and ash determination by proximate analysis of coal seams of the Rio Bonito Formation obtained from 5 well core profiles. The VR values were compared with the available desorption and adsorption volumes of gas, lithological and compositional data to understand the effect of intrusions on coal seams. The thermal halo dimension varies from 1 to 1.5 time the thickness of the igneous body. Both below and above the intrusion. The higher thermal halo was found in samples of the CBM001-CL-RS borehole. The analyses indicate that maceral and ash contents do not show significant change caused by the thermal halo, except for an increase in VRs near the igneous rock ranging from 1.0 to 5.0%Rr, reflecting thermal alteration by the intrusive bodies, forming natural coke near the contact. In samples not affected by the intrusion the VR range from 0.5 to 0.8%Rr, considered to reflect the values derived from burial history. Thermal calculations determined maximum paleotemperatures between 300 and 350 °C closer to the intrusion contact (2–5 m) and decreasing to average values within 100 ± 10 °C, with little or no effect of the intrusion heat. Unaffected samples of the Santa Terezinha Coalfield showed elevated paleotemperatures (120 ± 10 °C) compared to the other deposits, which implies higher subsidence rates or a local geothermal gradient increase. The content of CBM in coal seams generally increases with VRs and vitrinite volumes but decreases locally towards the contact with the intrusion. This behavior probably relates to the development of devolatilization vacuoles that reduce the adsorption surface of vitrinite macerals. There are seams with higher vitrinite contents that under proper thermal conditions, have more potential for gas generation and storage. The increase in depth and thickness of the coal seams also contribute to an increase in gas storage capacity. Highlights: Permian coalfields of southern Brazil were intruded by Cretaceous igneous rocks. Intrusive rocks created a thermal halo about to 1–1.5× the intrusion thickness. Elevated heat increased vitrinite reflectance, reaching the natural gas window. Secondary heat form natural coke, increasing porosity around the igneous contact. CBM deposits are undersaturated as indicated by desorption and adsorption data.